Stably maintained microtubules protect dopamine neurons and alleviate depression-like behavior after intracerebral hemorrhage - Yang Yang (Nature Portfolio, 2018)
Abstract Mesolimbic dopamine (DA) system lesion plays a key role in the pathophysiology of depression, and our previous study demonstrated that reduced microtubule (MT) stability aggravated nigrostriatal pathway impairment after intracerebral hemorrhage (ICH). This study aimed to further investigate the occurrence regularity of depression-like behavior after ICH and determine whether maintaining MT stabilization could protect DA neurons in ventral tegmental area (VTA) and alleviate depression-like behavior after ICH. An intrastriatal injection of 20 μl of autologous blood or MT depolymerization reagent nocodazole (Noco) was used to mimic the pathology of ICH model in mice. The concentration of DA, number of DA neurons and acetylated α-tubulin (a marker for stable MT) in VTA were checked, and depression-related behavior tests were performed after ICH. A MT-stabilizing agent, epothilone B (EpoB), was administered to explore the effects of MT stabilization on DA neurons and depression-like behavior after ICH. The results showed that obvious depression-like behavior occurred at 7, 14, and 28 days (P < 0.01) after ICH. These time-points were related to significant decreases in the concentration of DA (P < 0.01) and number of DA neurons (P < 0.01) in VTA. Moreover, The decrease of acetylated α-tubulin expression after ICH and Noco injection contributed to DA neurons’ impairment in VTA, and Noco injecton also aggravate ICH-induced depression-like behaviors and DA neurons’ injury. Furthermore, EpoB treatment significantly ameliorated ICH and Noco-induced depression-like behaviors (P < 0.05) and increased the concentration of DA (P < 0.05) and number of DA neurons (P < 0.05) in VTA by increasing the level of acetylated α-tubulin. The results indicate that EpoB can protect DA neurons by enhancing MT stability, and alleviate post-ICH depressive behaviors. This MT-targeted therapeutic strategy shows promise as a bench-to-bedside translational method for treating depression after ICH.